The Causes of Political Violence and Terrorism on the Verge of the XX-XXI Centuries: The Basic Approaches - Tuhvatullin, Airat; Epshteyn, Vitaly; Imamutdinova, Albina (Journal of History Culture and Art Research, 2018)
One of the main problems of modern socio-political relations is the escalation of violence, which takes on a mass character and spreads even in the once safe regions of the world. In this regard, a special research interest is the identification of the causes of political violence in the form of terrorist actions. The objective of this paper is to characterize the main approaches of Western researchers to determine the causes of political violence and terrorism in public life at the turn of the XX and XIX centuries, and to reveal the influence of various factors on the spread of political terrorism in the modern world. The main approaches to the study of the problem posed were the analytical method and content analysis. The paper shows that the natural causes of social tension and growth of terrorist movements should be eliminated with the help of educational and socially oriented policies of the state and the world community of nations as a whole. The materials of this paper can help further study the specifics of political violence and take preventive measures against terrorism by power structures and law enforcement agencies.